The Behavior Teachers of Raudhatul Athfal (RA) with Achievement in the Golden Age - Noor, Fu'ad Arif (Universitas Negeri Semarang, 2020)
This study emphasizes on the behavior of outstanding RA teachers who can be limited as mental states to think, behave, and behave during the golden age in the growth and development of an early child when RA teachers experience them. These behaviors are reflections of various aspects, both physical and non physical, as well as psychological reactions from an RA teacher with environmental achievements. These outstanding RA teachers during the golden age mostly did not receive formal education in their early age education, not through kindergarten (kindergarten) even those who were equal, but their childhood experiences really liked to play rain, play ball, even used to playing with boys (man). The teaching patterns instilled by his parents also tend to be rigid and decisive, especially his father who is also a teacher to teach him. In his house deliberately no television was provided because it was considered to be able to take up study time.